2018
DOI: 10.1177/0021998318780208
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of polylactic acid reinforced bagasse/basalt hybrid fiber composites

Abstract: This paper focuses on the mechanical behavior of Polylatic acid reinforced Basalt and Bagasse fibers. The most important aspect in formulating this hybrid composite with better mechanical properties is the optimization of interfacial bonding between the reinforcing bagasse fiber and basalt fiber and polymer matrix. The composite of different weight proportion of the materials is compounded using twin screw extruder. The specimens were prepared by injection molding and subjected to various mechanical testing un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Different aspects of the PLA/RH6 and RH6‐KH550/KH570 composites were observed, with the appearance of some voids and cracks (Figure 6c–f), and the morphology of the interface between fibers and matrix was also studied. These features directly affect the permeability and mechanical property 45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different aspects of the PLA/RH6 and RH6‐KH550/KH570 composites were observed, with the appearance of some voids and cracks (Figure 6c–f), and the morphology of the interface between fibers and matrix was also studied. These features directly affect the permeability and mechanical property 45 …”
Section: Resultsmentioning
confidence: 99%
“…These features directly affect the permeability and mechanical property. 45 As shown in Figure 6c,e, it was found that some agglomerations and voids appeared on the surfaces of the two composites, which may be caused by poor adhesion/ bonding at the interface region. The condition of the RH6-KH550/KH570 composite was better than that of PLA/RH6 composite, the MNRH fibers were well involved in PLA matrix and distributed more homogeneously(Figure 6c,e).…”
Section: Microstructural Of Pla and Its Compositesmentioning
confidence: 85%
“…The fiber loading of 40 wt% with jute and banana fiber weight ratio of 1:1, 3:1, and 1:3 improves the micro‐hardness values by 113%, 123%, and 97%, respectively. King et al (2019) [ 219 ] conducted a mechanical properties analysis of PLA reinforced basalt/bagasse hybrid polymer composites. The results reveal that maximum tensile, flexural and impact strengths were noted at 52.8 MPa, 82.2 MPa and 3.39 kJ/m 2 , respectively.…”
Section: Characterization Of Natural Fiber Reinforced Polymer Matrix ...mentioning
confidence: 99%
“…10 Besides carbon and glass fibers, the researchers employed basalt fiber as reinforcement because of its exceptional chemical, mechanical, and physical characteristics. [11][12][13][14][15][16] Wang X. 17 and Dhand V. et al 12 also stated interesting mechanical, thermal, and electrical properties of basalt fiber composites compared to glass fiber composites.…”
Section: Introductionmentioning
confidence: 99%